Effect of Weight Loss on Symptoms of Polycystic Ovarian Syndrome among Women of Reproductive Age - Anita Dileep; Manal Ahmed Faek Samy; Nazneen Hussain; Sham Zain Alabdind (Dubai Medical Journal)
Background: The polycystic ovarian syndrome (PCOS) is a common endocrine disease, which affects women of childbearing age. Its exact etiology is not yet fully understood, but there have been a number of theories and hypotheses which suggested that it is related to multiple factors. However, the most common cause is the insulin resistance, which contributed in development of PCOS and weight gain as well. Aim: This study aims to assess the impact of weight control on the management of PCOS among obese patients. Methods: This is a retrospective observational study conducted on 68 obese PCOS women at different primary healthcare centers in Dubai. Patients were included only if they were following a healthy lifestyle, using metformin (750–1,000 mg) for at least 3–9 months, and lost at least 5.0–10.0% of their baseline body weights. The follow-up period was for 1 year based on their medical records. Data were analyzed and represented as mean ± standard deviation of continues measures, while the χ2 test, independent Student’s t test, and one-way ANOVA test were performed for comparing numerical variables between different groups of categorical variables. p value was considered significant at <0.05. Results: Mean age of the patients was 26.1 ± 6.5 years, and the average baseline BMI was 34.7 ± 4.3 kg/m2. The most frequently reported clinical feature of PCOS was irregular menstruation (n = 38, 55.9%). Majority of the patients (80.0%) who had a successful weight loss (median of 8.0 [3, 10] kg) during the 1-year follow-up reported a significant clinical improvement, while those reported no clinical improvement did not actually have a considerable weight loss (median of 4 [2, 5] kg) (p < 0.001). Additionally, the duration of treatment of 9 months was significantly respectable for achieving higher weight loss than less durations (p = 0.002). Furthermore, the only factor which contributed to clinical improvement of PCOS was the baseline BMI (p < 0.001). Conclusion: This study demonstrated that following an appropriate care plan by a combination of lifestyle modifications and metformin was effective in achieving a successful weight loss, which resulted in a significant improvement in the clinical features of the PCOS. Further studies are recommended to raise awareness of women regarding the PCOS and to encourage them to communicate with healthcare providers for initiating their self-management care.